Development of Serotonergic Fibers in the Post-Natal Mouse Brain - Maddaloni, Giacomo; Bertero, Alice; Pratelli, Marta; Barsotti, Noemi; Boonstra, Annemarie; Giorgi, Andrea; Migliarini, Sara; Pasqualetti, Massimo (Frontiers in Cellular Neuroscience, 2017)
Serotonin-synthetizing neurons, which are confined in the raphe nuclei of the rhombencephalon, provide a pervasive innervation of the central nervous system and are involved in the modulation of a plethora of functions in both developing and adult brain. Classical studies have described the post-natal development of serotonergic axons as a linear process of terminal field innervation. However, technical limitations have hampered a fine morphological characterization. With the advent of genetic mouse models, the possibility to label specific neuronal populations allowed the rigorous measurement of their axonal morphological features as well as their developmental dynamics. Here, we used the Tph2GFP knock-in mouse line, in which GFP expression allows punctual identification of serotonergic neurons and axons, for confocal microscope imaging and we performed 3-dimensional reconstruction in order to morphologically characterize the development of serotonergic fibers in specified brain targets from birth to adulthood. Our analysis highlighted region-specific developmental patterns of serotonergic fiber density ranging from a linear and progressive colonization of the target (Caudate Putamen, Basolateral Amygdala, Geniculate Nucleus and Substantia Nigra) to a transient increase in fiber density (medial Prefrontal Cortex, Globus Pallidus, Somatosensory Cortex and Hippocampus) occurring with a region-specific timing. Despite a common pattern of early post-natal morphological maturation in which a progressive rearrangement from a dot-shaped to a regular and smooth fiber morphology was observed, starting from post-natal day 28 serotonergic fibers acquire the region specific morphological features present in the adult. In conclusion, we provided novel, target-specific insights on the morphology and temporal dynamics of the developing serotonergic fibers.